Long Non-coding RNA ASNR Targeting miR-519e-5p Promotes Gastric Cancer Development by Regulating FGFR2 - Chen, Zihao; Li, Yong; Tan, Bibo; Li, Fang; Zhao, Qun; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; Liu, Yu; Wang, Dong (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer (GC) is one of leading causes of cancer-related death worldwide. Long non-coding RNAs (lncRNAs), a novel class of transcripts, have gained significant attention in current research field such as carcinogenesis. However, the mechanisms of the clinical significance of most lncRNAs in human cancer are mainly undocumented. This research desires to explore the clinical significance, biological function, and mechanism of Lnc_ASNR (apoptosis suppressing-noncoding RNA) in GC. Cell proliferation, cell cycle, cell migration and invasion abilities were respectively determined by 3-(4,5Dimethylthiazol-yl)-2,5Dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT), flow cytometry, wound healing, and transwell assay. The luciferase reporter assay was used to verify the targeting relationships between Lnc_ASNR, miR-519e-5p, and FGFR2. The tumor xenograft assay was conducted to confirm the results of cell experiments. qRT-PCR revealed that Lnc_ASNR was highly expressed in GC cells and tissues. Down-regulated Lnc_ASNR could reduce proliferation, migration and invasion in GC cells, while up-regulated Lnc_ASNR could promote the cell proliferation, migration and invasion. Moreover, the effect of Lnc_ASNR on migration and invasion ability is closely related to epithelial-mesenchymal transition (EMT). The bioinformatics analysis, luciferase assay, and Western blot indicated that Lnc_ASNR inhibited miR-519e-5p expression but increased fibroblast growth factor receptor 2 (FGFR2) expression. Lnc_ASNR and FGFR2 had a common target (miR-519e-5p) and were negatively related to miR-519e-5p expression. Our findings suggested that Lnc_ASNR functioned as a ceRNA targeting miR-519e-5p and facilitated GC development by regulating the pathway of miR-519e-5p/FGFR2.